(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract The research aims to identify tax exemptions, their objectives and types, as well as to shed light on the concept of sustainable development, its objectives, dimensions and indicators (economic, social and environmental), as well as to analyze the relationship between tax exemptions and economic development, in addition to measuring and analyzing the impact of tax exemptions on economic development in Iraq for the period ( 2015 - 2021) using the NARDL model. The research problem centers on the fact that failure to employ financial policy tools correctly led to a weakness in achieving economic justice, which leads to a failure to improve social welfare and an unfair distribution of natural resources. Do tax exemptions affect the achievement of economic development in Iraq, and to prove the research hypothesis, the research sample represented a group of companies covered by tax exemptions, numbering six companies. The financial data was studied and analyzed and its impact on the average per capita GDP as an indicator of economic development in Iraq for the period (2015-2021), and the research concluded that there is There is a long-term, non-linear positive relationship between corporate tax exemptions and economic development in Iraq. Increasing corporate tax exemptions by (1%) will lead to an increase in economic development in Iraq by (0.798%), while decreasing tax exemptions by (1%) will lead to a decrease in economic development in Iraq by (0.798%). (1.179%), and the research recommends It is necessary to direct exemptions towards vital economic sectors to encourage investment in them that contribute to increasing the gross domestic product and thus its average per capita share to achieve economic development in Iraq.